COSTS OF A STAFF COMMUNICATION INTERVENTION TO REDUCE DEMENTIA BEHAVIORS IN NURSING HOME CARE. (30th June 2017) - Williams, K.N.; Ayyagari, P.; Perhounkova, Y.; Bott, M.; Herman, R.; Bossen, A.L.
Abstract: Background: Persons with Alzheimer's disease and other dementias experience behavioral symptoms that frequently result in nursing home (NH) placement. Managing behavioral symptoms in the NH increases time required to complete care, adds to staff stress and turnover, and increases costs of care. The Changing Talk (CHAT) intervention improves staff communication by reducing elderspeak and led to reduced resident resistiveness to care (RTC). We evaluated the cost effectiveness of CHAT in reducing elderpeak and RTC. Methods: Costs to provide CHAT were determined for each NH (N=11) using process based costing. Analysis: Based on the number and type of staff attending the CHAT training, and materials and interventionist time, an average cost per participant was calculated for each NH. Regression estimates from the parent study were applied to determine costs per unit reductions in staff elderspeak and resident RTC. Results: A one percentage point decrease in elderspeakwas associated with an average 0.43 reduction in RTC. CHAT led to a 12.9% average drop in elderspeak use by NH staff. The average 12.9% reduction in staff elderspeak use predicted a 5.59% decrease in RTC per resident. Assuming that each staff cares for 2 residents with RTC, the cost effectiveness ratio for each 1% RTC reduction per resident is 7.13. Conclusions: Cost variations to reduce elderspeak and RTC were based on the number of factors such as baseline elderspeak and the number of residents with RTC. Overall, the 3-session CHAT program is a cost-effective intervention for reducing RTC in dementia care.